Socio-Cultural Factors Affecting the Performance of Women Entrepreneurs in Adaklu Waya in the Volta Region of Ghana - Senna, Richard; Agbolosoo, Dela Eyaakor Enuameh (Technium Social Sciences Journal, 2021)
Female entrepreneurs have been observed to contribute to nations’ economic progress in recent years, particularly in rural regions, with a large proportion of SMEs in Ghana held by women. Unfortunately, the contribution of female entrepreneurs to economic progress has been under-reported and, to some extent, overlooked for decades. Part of the explanation is that most female entrepreneurs labor in the informal market, which is fraught with difficulties. The purpose of this study was to determine the socioeconomic elements that influence the performance of female entrepreneurs in Adaklu Waya, a rural town in Ghana’s Volta Region. The data was collected from 40 female entrepreneurs in the Adaklu Waya neighborhood utilizing a mixed method approach that included surveys and face-to-face interviews. The study discovered a number of societal and cultural barriers that prevent women from starting small businesses. Age, educational level, marital status, family size, lack of experience, male dominance, household roles and expectations, childbearing roles, and the patriarchal nature of society were among the major social and cultural constraints limiting women’s development and success as entrepreneurs, according to respondents. The study’s findings, as well as others, have policy implications for female entrepreneurship. As a result, there is a call for coordinated policies to address these challenges, such as the development of specific women-centered policies and programs to cater for and ensure women’s entrepreneurial development, the inclusion of entrepreneurship and innovation in the formal educational curriculum in schools, and the creation of specific credit programs for women entrepreneurs by financial institutions. Furthermore, societal negative perceptions regarding successful women in business must be dispelled. These would aid in encouraging and promoting female entrepreneurship, allowing this crucial demographic to become catalysts for job creation, poverty reduction, and socioeconomic growth.